Analysis of the Chemical, Antioxidant, and Anti-Inflammatory Properties of Pink Pepper (Schinus molle L.) - Min Jeong Kim; Dae Won Kim; Ju Gyeong Kim; Youngjae Shin; Sung Keun Jung; Young-Jun Kim (MDPI AG, 2021)
Here, we compared the chemical properties and antioxidant effects of black pepper (Piper nigrum L.) and pink pepper (Schinus molle L.). Additionally, the antioxidant and anti-inflammatory capacities of pink pepper were measured to determine nutraceutical potential. Pink peppers from Brazil (PPB), India (PPI), and Sri Lanka (PPS) had higher Hunter a* (redness) values and lower L* (lightness) and b* (yellowness) values than black pepper from Vietnam (BPV). Fructose and glucose were detected in PPB, PPI, and PPS, but not in BPV. PPB, PPI, and PPS had greater 2,2-diphenyl-1-picrylhydrazyl and 3-ethylbenzothiazoline-6-sulphonic acid radical scavenging stabilities and higher total phenolic contents than BPV. BPV had higher levels of piperine than the pink peppers. Gallic acid, protocatechuic acid, epicatechin, and p-coumaric acid were detected only in the three pink peppers. PPB significantly suppressed lipopolysaccharide-induced reactive oxygen species production with increased Nrf2 translocation from cytosol to nucleus and heme oxygenase-1 expression. PPB and PPS significantly suppressed lipopolysaccharide-induced nitrite production and nitric oxide synthase expression by suppressing phosphorylation of p38 without affecting cell viability. Additionally, PPB and PPS significantly suppressed ultraviolet B-induced cyclooxygenase-2 expression by affecting the phosphorylation of ERK1/2 without cell cytotoxicity. These results suggest that pink pepper is a potential nutraceutical against oxidative and inflammatory stress.